Fibrin/fibrinogen degradation products in cerebrospinal fluid of patients admitted to a psychiatric unit. Issue 3 (March 1974) - Hunter, Richard; Thomson, Thomas; Reynolds, C. M.; Pitcher, Pamela M.
Abstract : Paired cerebrospinal fluid (CSF) and serum samples collected from 81 of 241 patients admitted to a district psychiatric hospital during a six month period were assayed for fibrin/fibrinogen degradation products (FDP) using a haemagglutination inhibition technique. FDP were found in all serum samples. Fifteen patients (18·5%) had FDP in the CSF (range 0·7-3·75 μg/ml.) and of these 13 (87%) had associated CSF protein abnormalities and 9 (60%) were hypertensive. Mean serum FDP values were the same (4·4 μg/ml.) in patients with and without FDP in the CSF. Three patients had raised serum FDP concentrations but no FDP in the CSF. The evidence suggests that the presence of FDP in CSF indicates recent central nervous system damage. In this series the most common cause was vascular disease.